2017
DOI: 10.1002/polb.24326
|View full text |Cite
|
Sign up to set email alerts
|

Precise synthesis of a series of poly(4-n-alkylstyrene)s and their glass transition temperatures

Abstract: Poly(4-n-alkylstyrene)s with six kinds of n-alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and octyl groups covering wide molecular weight range from around 5 k to over 100 k were precisely synthesized by living anionic polymerizations. It was confirmed that all the polymers obtained have narrow molecular weight distribution, that is, M w /M n is all less than 1.1, by SEC. T g s of all the polymers were estimated by DSC measurements and it turned out to be clear that their molecular weight dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…We conducted a literature search and found that most of the reported T g,∞ values fell below ∼ 500 K (Brandrup et al, 1999;Fox Jr. and Flory, 1950;Onder et al, 1972;Montserrat and Colomer, 1984;Papadopoulos et al, 2004;Matsushima et al, 2017). The Fox-Flory equation works very well for high-molarmass compounds and is also generally applicable to smaller compounds , as supported by an approximately linear dependence of T g on the inverse molar mass in Fig.…”
Section: Introductionmentioning
confidence: 86%
“…We conducted a literature search and found that most of the reported T g,∞ values fell below ∼ 500 K (Brandrup et al, 1999;Fox Jr. and Flory, 1950;Onder et al, 1972;Montserrat and Colomer, 1984;Papadopoulos et al, 2004;Matsushima et al, 2017). The Fox-Flory equation works very well for high-molarmass compounds and is also generally applicable to smaller compounds , as supported by an approximately linear dependence of T g on the inverse molar mass in Fig.…”
Section: Introductionmentioning
confidence: 86%
“…Degree of polymerizations, DPs, were determined from M w s divided by molecular weights of monomers. Poly(4‐ n ‐alkylstyrene) samples were coded as PC m St_ X following the same manner adopted in the previous article, where m and X denote the number of carbon atom in n ‐alkyl side group and the molecular weight, respectively. For instance, PC1St_6 expresses poly(4‐methylstyrene) with molecular weight of 6 kg/mol.…”
Section: Methodsmentioning
confidence: 99%
“…Syntheses and characterization of all the poly(4-n-alkylstyrene)s used in the present work were already reported in a Additional Supporting Information may be found in the online version of this article. previous article, 32 and their molecular characteristics are summarized in Table 1. Polyisoprenes were also synthesized by living anionic polymerizations in benzene using sec-BuLi as an initiator at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations